2010
DOI: 10.1253/circj.cj-10-0261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renin-Angiotensin System Inhibitors on the Occurrence of Acute Kidney Injury Following Off-Pump Coronary Artery Bypass Grafting

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp s the indications for renin-angiotensin system (RAS) inhibitors expand for secondary prevention in patients with coronary artery disease, 1 an increasing number of patients presenting for coronary artery bypass graft surgery (CABG) have had chronic angiotensin-converting enzyme inhibitor or angiotensin receptor blocker administration. Although continued RAS inhibitor therapy is associated with improved survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…Our findings regarding the prognostic utility of angiotensinogen as a biomarker of AKI suggest that the RAS could be mechanistically involved in AKI. This is supported by observational studies that have noted an association between pharmacologic inhibition of the RAS and risk of developing AKI, although there are conflicting reports in the literature (31)(32)(33)(34). The ACE II genotype has been associated with increased risk of AKI in the ICU (35).…”
Section: Discussionmentioning
confidence: 85%
“…Our findings regarding the prognostic utility of angiotensinogen as a biomarker of AKI suggest that the RAS could be mechanistically involved in AKI. This is supported by observational studies that have noted an association between pharmacologic inhibition of the RAS and risk of developing AKI, although there are conflicting reports in the literature (31)(32)(33)(34). The ACE II genotype has been associated with increased risk of AKI in the ICU (35).…”
Section: Discussionmentioning
confidence: 85%
“…24 The medullary region in the kidney exists on a hypoxic precipice as a result of low blood flow and countercurrent exchange of oxygen, although paradoxically housing nephron segments with very high energy requirements (eg, the S3 segment of the proximal tubule). The ischemic state after cardiac surgery worsens the relative hypoxia, leading to prolonged cellular injury and cell death in these predisposed tubule segments.…”
Section: Discussionmentioning
confidence: 99%
“…[44], Ouzounian et al [37], and Yoo et al [45], studied 11330, 1647, and 472 cardiac surgery patients, respectively, and demonstrated no significant association between preoperative ACEi/ARB use and AKI. However, all three studies observed a non-significant trend towards a benefit with preoperative ACEi/ARB use raising the possibility of insufficient statistical power to detect the association [37,44,45]. …”
Section: Discussionmentioning
confidence: 99%